Design of Letter Management System at Kanna Utara Village Office Based on Website - Syahratul Annas; Isdayani B; Rahmat Siswanto (Brilliance: Research of Artificial Intelligence, 2025)
This study aims to design a correspondence management system in the Kanna Utara village office based on a website that previously used manual methods through bookkeeping and Microsoft Word/Excel applications; these methods have various weaknesses, such as easy archive damage, limitations in searching for letters, and potential data loss. The system, which was designed using the Laravel framework with an agile development approach, aims to improve efficiency, security, and ease of access for both village officials and the community. This qualitative research approach uses observation and interviews to identify user needs, such as digital management of incoming and outgoing letters, online submission by the community, and tracking of letter status in real time. This system has separate features between Kanna Utara village office employees and the community to ensure access authority according to their respective roles. Kanna Utara village office employees can monitor and manage letters through the admin dashboard, and the community can submit letter requests and view letter status on the public dashboard. The simple interface makes it easy for village officials with technical limitations to operate the system. Although the system is running well, development, such as digital signatures and automatic notifications via short messages, is still needed. This study concludes that digitalizing the correspondence system at the village level is possible and can be used as a model for other villages with similar conditions.